Pandangan Tuan Guru terhadap Pencegahan Perkawinan oleh Wali Nasab dalam Putusan Pengadilan Agama Selong Perspektif Teori Maqashid Syari’ah: Studi Kasus Di Lombok Timur - Muhammad Badaruddin; Teti Indrawati Purnama Sari; Zainal Arifin Haji Munir (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Marriage laws in Indonesia for the Muslim community are regulated in the Compilation of Islamic Law (HKI). It does not rule out the possibility that disputes may arise during the marriage process. Two people who love each other and want to carry out the orders of Allah and His Messenger, also want to realize article 3 in the Compilation of Islamic Law, are prevented by their own lineage guardian because they do not agree with their child's marriage. This conflict occurred because there was a gap in legal remedies for family guardians who did not agree with their child's marriage, as well as legal remedies for women whose guardians were reluctant to become guardians for their marriage. This research is field research with qualitative research methods that are descriptive analysis. The approach used in this research is a case approach. The object of study in this research is the Selong Religion's decision regarding the prevention of marriage by lineage guardians. This research concludes that Tuan Guru's view regarding the prevention of marriage by the guardian of the lineage in the decision of the Selong Religious Court is that the prevention carried out by the guardian of the lineage in the decision of the Selong Religious Court is permissible as long as from the point of view of the guardian of the lineage it is possible that it will cause harm if the marriage continues to take place. Tuan Guru in East Lombok views the prevention of marriages carried out by nasab guardians in the decision of the Selong Religious Court from the perspective of the case, Islamic religion, custom and social. The Tuan Gurus also support the position of religious guardians who prevent the marriage of their children in the decision of the Selong Religious Court.